R&D centres of excellence in Canada - Ensign, Prescott C.; Birkinshaw, Julian M.; Frost, Tony S. (Université d'Ottawa | University of Ottawa, 2000)
This chapter examines CoEs in the context of the R&D operations of foreign subsidiaries in Canada. Its aim is to provide some background on the literature on foreign-owned R&D operations in Canada, and then to provide evidence from the authors’ current research on this topic. To some extent the ‘centre of excellence’ terminology is a case of old wine in new bottles, in that there has been a steady stream of research over the past thirty years concerned with understanding the R&D activities of foreign firms in Canada. However, the CoE terminology does also add something, in that it helps to clarify the role of R&D centres within their corporate system, and the conditions under which they are able to deliver on that role. The guiding research questions for this chapter are two. What is the evidence for R&D CoEs in foreign-owned subsidiary companies in Canada? And what are the factors that are associated with their existence? The chapter is in two parts. The first part draws on the existing literature—both literature concerned with the development of CoEs in multinational firms and the literature that looks specifically at R&D in Canada. The second part is written on the basis of our recent empirical research in this area. Specifically, it reports on a survey of 99 foreign-owned subsidiaries in Canada, and on a series of case-study interviews conducted by the authors over the last five years.